New security approach in real-time wireless multimedia sensor networks - Msolli, Amina; Helali, Abdelhamid; Maaref, Hassen (Computers & electrical engineering, 2018)
•A new approach Shift-AES modifies the AES algorithm to make it compatible with WMSN.•The proposed algorithm was developed on the AES with new Shift-Columns transformation.•Studies of Shift-AES maintain a better safety and a decrease in execution time of CPU.•A comparison is made between the Shift-AES and the algorithms existing literature. Real time multimedia applications are increasingly achieving success in the everyday world. A diversity of applications has appeared in the wireless sensor network, where the energy consumption is a very important factor in wireless multimedia sensor networks (WMSN) to increase network lifetime. Thus, multimedia data transmission relies on safety to protect personal life. However, because of constraints, the standard encryption algorithms are not compatible with this domain. This article investigates a new approach called Shift-Advanced Encryption Standard (Shift-AES). This approach modifies the AES algorithm to make it compatible with WMSN. Experimental studies of the new approach maintain a better level of safety with a decrease in execution time of the Central Processing Unit. A comparison is made between the new approach and the algorithms in the existing literature.